Change of Helicobacter pylori prevalence in a decade among children undergoing endoscopy - Yaman, Aytaç; Kuloğlu, Zarife; Kahveci, Ahmet; Sayıcı, Ufuk; Ensari, Arzu; Kansu, Aydan (The Turkish Journal of Pediatrics, 2016)
Our aim was to investigate the trend of H. pylori infection among children during the last decade by a retrospective analysis. Reports of children in whom esophago-gastroduodenoscopy was performed at our institution during two periods 2002-2003 and 2012-2013 were seperated into Group I and Group II, respectively. Pathology reports were investigated for gastritis, atrophy and H. pylori presence. A total of 380 children, 131 in Group I and 249 in Goup II were recruited in the study. H. pylori postivity was found to be higher in Group I (% 48.1 and % 23.1, respectively, p < 0.001). Gastritis and atrophy were associated with H. pylori and both were more prevalent in Group I (p < 0.001). Our study demonstrates that H. pylori prevalence is decreasing in a pediatric population undergoing EGD in Ankara. This is the most recent study regarding pediatric H. pylori prevalence change in Turkey that we know of.